Inequality, taxation and intergenerational transmission - Bishop, John A.; Rodríguez, Juan Gabriel (Research on economic inequality ;, 2018)
Research on Economic Inequality, volume 26, primarily contains papers presented at the 8th Society for the Study of Economic Inequality (ECINEQ) meeting. The papers cover such topics as the effect of inheritance taxation on the "pre-distribution" of income, and tax progressivity under alternative inequality definitions. Other papers address the evolution of wealth inequality (Piketty's "r-g"), the decomposition of the determinants of wage bi-polarization, a multidimensional analysis of food insecurity in Israel, and the "paradox of progress" (educational) in Latin America. Three papers address the intergenerational transmission of inequality, two of which focus on Europe and one which considers a wide variety of countries. The final two papers explore inequality (mis) perceptions and the influence of the political structure on stated inequality preferences.